2011
DOI: 10.4103/0974-2700.82200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ondansetron and combination of ondansetron and dexamethasone as a prophylaxis for postoperative nausea and vomiting in adults undergoing elective laparoscopic surgery

Abstract: Background:Laparoscopic surgeries are the second most common cause of postoperative nausea and vomiting (PONV), which would cause unexpected delay in hospital discharge. This study intends to compare the efficacy and safety of the combination of ondansetron and dexamethasone with ondansetron alone given as prophylaxis for PONV in adults undergoing elective laparoscopic surgery.Materials and Methods:One hundred adult patients undergoing elective laparoscopic surgeries were selected and were randomly divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 12 publications
3
19
2
Order By: Relevance
“…The results of our study are in agreement with other studies conducted by various authors [12][13][14][15][16][17] .…”
Section: Discussionsupporting
confidence: 83%
“…The results of our study are in agreement with other studies conducted by various authors [12][13][14][15][16][17] .…”
Section: Discussionsupporting
confidence: 83%
“…This is comparable to the study conducted by Bhattarai et al 12 and Panda et al 14 . Lopez-Olando et al 15 concluded that prophylactic administration of a combination of dexamethasone and ondansetron is effective in In this study, ondansetron 4 mg was used as rescue anti emetic in both the groups.…”
supporting
confidence: 81%
“…The mechanism of action of dexamethasone is unknown; however there have been some suggestions, such as central/ peripheral inhibition of production of 5 HT, central inhibition of synthesis of prostaglandins, or changes in permeability of the blood brain barrier to serum protein 7,12 . The major concern regarding use of dexamethasone is infection, delayed wound healing and other side effect.…”
mentioning
confidence: 99%
“…D'Souza et al compared dexamethasone with ondansetron for the prevention of PONV after laparoscopic gynecologic surgery and found that dexamethasone decreased the incidence of PONV and use of single dose of dexamethasone was safe, had a lesser cost and could be alternative to single dose ondansetron in this patient population 19 . Bhattarai et al compared use of ondansetron alone with combined use of 4 mg ondansetron plus 8mg dexamethasone in the control of PONV in patients undergoing laparoscopic surgery and found that the combined use of two agents was more effective 25 . The combination was also safe and well tolerated by the patients.…”
Section: Discussionmentioning
confidence: 99%